Overcoming overwork - Schnaubelt, Teri (Women at work, 2024)
Overworked? Overwhelmed? You're not alone. The amount of work placed on women is often insurmountable. Along with doing what's required for their jobs, women are frequently also asked to take on tasks that don't lead to growth or promotion, and to manage other forms of invisible labor at work and at home. All of this can leave women feeling underappreciated, frustrated, and burned out. We need to end the culture of overwork for women. From saying no to office housework to setting your own priorities, Overcoming Overwork provides practical advice for taking back your time so that you can use it for what matters to you.